Learning Styles, Does it Cause the Differences of Students Achievement? - Barokah, Sarah Mustika; Suseno, Loviniantika Cahyaning; Deze Say, Yosepha Kurniawati; Mustadi, Ali (Universitas Negeri Malang, 2019)
This research aims to examine the difference between the learning achievement of students with learning styles visual, auditory, and kinesthetic in Sub-district Sukun Malang. The type of this research was comparative quantitative. This research population was all 4th-grade students in Sub-district Sukun, which amount to 3250 students, while the technique of sample retrieval used random cluster sampling. Sample of this research amount to 338 of the 4th-grade students from 5 elementary schools in Sub-district Sukun. Data were collected by using learning style questionnaires and documents of students learning achievement. Data analysis of this research used quantitative statistics descriptive and analysis statistics nonparametric using the Kruskal-Wallis Test. The result of this research showed that the amount of significant value is 0.688, higher than 0.05, so it can be concluded that there is no difference in thematic learning achievement between a student who has visual, auditory, and kinesthetic learning styles.